ALBUMINURIA IS ASSOCIATED WITH LESS EFFORT TOLERANCE IN HYPERTENSION AND DIABETES - Maria Rodrigues Daniel, Juliana; Roberto Neres Meira, Tani; de Fatima Meira, Marcia; Garcia Zanati Bazan, Silméia; Jorge da Silva Franco, Roberto; Barretti, Pasqual; Cuadrado Martin, Luis (Health and Society, 2024)
Introduction: The presence of albuminuria is an adverse marker of renal dysfunction progression. Hypertension and diabetes mellitus predispose to albuminuria. However, not all hypertensive and diabetic patients have albuminuria, so it is relevant to identify risk factors associated to this abnormality. The acute effect of intense physical activity may lead to transient albuminuria. On the other hand, physical inactivity is associated with risk factors for albuminuria Objective: To analyze the association between activity levels or physical performance and albuminuria in hypertensive and/or diabetic patients treated at basic health services. Methodology: A prospective cross-sectional study with hypertensives and/or diabetics subjects. The patients were evaluated in regard of albuminuria, clinical, laboratory and physical test performance variables. Results: There was no association between the degree of albuminuria and demographic, anthropometric, laboratory variables, functional capacity and level of physical activity. The degree of albuminuria was associated with systolic blood pressure, as well as the perception of effort, obtained by Borg Scale during the test in univariate analysis (odds ratio 4.11 with 95% confidence interval from 1.18 to 14.37, p = 0.027) and adjusted for systolic blood pressure and diabetes (odds ratio 3.02 with 95% confidence interval from 1.35 to 6.75; p = 0.007). Conclusion: there was association between albuminuria and perceived effort, as well with systolic blood pressure. There was not with association physical performance or level of activity. Further studies are needed to elucidate the association of albuminuria with Borg Scale.